Advances in light manipulation in greenhouse horticulture: the innovative smart covers - Zamani, Farzaneh; Duri, Luigi Giuseppe; Mori, Mauro; Paradiso, Roberta (Frontiers in Plant Science, 2025)
Greenhouses play a key role in modern agriculture by creating controlled environments to fulfil specific plant climatic requirements, allowing the extension of the growing season and improving the crop productivity and product quality. Light, in terms of quantity (intensity), quality (spectral composition), and duration (photoperiod), is a crucial factor in driving plant performance in protected cultivation. Solar radiation is significantly affected by the greenhouse framework and cover material. The use of smart materials, including diffusive, photoselective, luminescent, and switchable covers, can positively modify the light intensity, spectrum, and distribution, improving the greenhouse light environment, hence the plant growth, morphology, and metabolism. This review summarizes the state of art of research on innovative covers suitable for modern greenhouse horticulture and their effects on plant performance in vegetable and ornamental crops.